2022
DOI: 10.1038/s41598-022-06237-0
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming cognitive set bias requires more than seeing an alternative strategy

Abstract: Determining when to switch from one strategy to another is at the heart of adaptive decision-making. Previous research shows that humans exhibit a ‘cognitive set’ bias, which occurs when a familiar strategy occludes—even much better—alternatives. Here we examined the mechanisms underlying cognitive set by investigating whether better solutions are visually overlooked, or fixated on but disregarded. We analyzed gaze data from 67 American undergraduates (91% female) while they completed the learned strategy-dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The cognitive set is a state of readiness or behavioral tendencies for an activity. 30 When renal dialysis patients experience a blow of disease or a failure in self-management, if they are accustomed to attributing these to fate or deficiencies in self-efficacy, they will develop the cognitive set that no external factors or person can change the results and tend to fall into a continuous state of helplessness. [19][20][21]27…”
Section: Negative Cognitive Setmentioning
confidence: 99%
“…The cognitive set is a state of readiness or behavioral tendencies for an activity. 30 When renal dialysis patients experience a blow of disease or a failure in self-management, if they are accustomed to attributing these to fate or deficiencies in self-efficacy, they will develop the cognitive set that no external factors or person can change the results and tend to fall into a continuous state of helplessness. [19][20][21]27…”
Section: Negative Cognitive Setmentioning
confidence: 99%
“…For example, in the Learned Strategy-Direct Strategy task only ~ 1 in 10 Americans between the ages of 7–68 electively switched from a learned solution to a better alternative 34 , 36 . Even after watching a video demonstrating the better strategy, many American undergraduates did not relinquish their familiar strategy 37 . However, intriguingly Pope et al 35 found that semi nomadic Namibian Himba pastoralist adults were ~ 4 times more likely to find and use the more efficient strategy than American adults.…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive set bias, the tendency to persist with a familiar strategy despite the availability of a better alternative, is found in a range of cognitive domains including mathematics [21][22][23][24] , design and engineering 25,26 , strategic reasoning 27 , tool-use 28,29 , as well as insight 30,31 , lexical 24,32 , and sequential problem-solving [33][34][35][36][37][38] . For example, in the Learned Strategy-Direct Strategy task only ~ 1 in 10 Americans between the ages of 7-68 electively switched from a learned solution to a better alternative 34,36 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the Learned Strategy-Direct Strategy task only ~ 1 in 10 Americans between the ages of 7-68 electively switched from a learned solution to a better alternative 34,36 . Even after watching a video demonstrating the better strategy, many American undergraduates did not relinquish their familiar strategy 37 . However, intriguingly Pope et al 35 found that semi nomadic Namibian Himba pastoralist adults were ~ 4 times more likely to nd and use the more e cient strategy than American adults.…”
Section: Introductionmentioning
confidence: 99%